2015
DOI: 10.1016/j.rpped.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Apoio ao aleitamento materno pelos profissionais de saúde: revisão integrativa da literatura

Abstract: Objective:To review the literature in order to evaluate how health professionals promote and support breastfeeding.Data sources:Studies from the following databases were retrieved: Scopus, PubMed, MEDLINE, Lilacs, SciELO, Web of Science and Cumulative Index to Nursing and Allied Health Literature (Cinahl). The descriptors “breastfeeding”, “professional role” and “patient care team” were used in the research. The review was limited to articles in Portuguese, Spanish, and English published between 1997 and 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
83

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 22 publications
0
15
0
83
Order By: Relevance
“…Health professionals should try to focus on the daily experiences of postpartum women, helping them to identify the best actions for the promotion of healthy breastfeeding (13) . Another study on the interaction of health professionals and mothers conducted in the inland of São Paulo, in a Neonatal Intensive Care Unit showed that the assistance provided by health professionals is not always positive and pleasant.…”
Section: [] I Tried To Breastfeed But Failed; I Could See Them Lomentioning
confidence: 99%
“…Health professionals should try to focus on the daily experiences of postpartum women, helping them to identify the best actions for the promotion of healthy breastfeeding (13) . Another study on the interaction of health professionals and mothers conducted in the inland of São Paulo, in a Neonatal Intensive Care Unit showed that the assistance provided by health professionals is not always positive and pleasant.…”
Section: [] I Tried To Breastfeed But Failed; I Could See Them Lomentioning
confidence: 99%
“…Essa prática é considerada uma medida facilitadora para o início do AM, prevista pela Portaria MS/GM nº 1.016/2003, (26) e embasa-se nas vantagens de estimular o AM sob livre demanda, favorecer os laços afetivos entre mãe e fi lho por meio do convívio precoce e contínuo, prevenir infecção hospitalar e possibilitar o cuidado da criança pela sua mãe, para facilitar o reconhecimento das necessidades do fi lho e o esclarecimento de dúvidas com os profi ssionais de saúde, fatores essenciais para o êxito da amamentação. (21) Nesse sentido, a disponibilidade de profi ssionais treinados para promoção e apoio ao AM durante a internação é fator fundamental para essa prática, especialmente em situações de difi culdades e/ou especiais, (27) como na presença de doenças maternas. No que se refere às doenças infectocontagiosas, o conhecimento sobre as repercussões dessas doenças para a…”
Section: Resultsunclassified
“…Os profissionais de saúde precisam ser mais capacitados para trabalhar com a promoção do aleitamento materno junto a adolescentes, seja por meio de instituições de ensino e formação, seja por meio de gestores da saúde, a fim de consolidar equipes multiprofissionais integradas e comprometidas com a saúde materna e infantil (19).…”
Section: Discussão E Conclusãounclassified